2019
DOI: 10.1002/pra2.172
|View full text |Cite
|
Sign up to set email alerts
|

#Cyberbullying in the digital age: Exploring people's opinions with text mining

Abstract: This study used text mining to investigate people's insights about cyberbullying. English‐language tweets were collected and analyzed by R software. Our analysis demonstrated three major themes: (a) the major actions that needed to be taken into consideration (e.g. guiding parents and teachers to cyberbullying prevention, funding schools to cope with cyberbullying), (b) certain events that were important to people (e.g. the Michigan cyberbullying law), and (c) people's major concerns in this regard (e.g. menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
1
5
0
1
Order By: Relevance
“…The proportion of negative and positive emotions was 24.4% and 10.8%, respectively. Similarly, Tahamtan and Huang found that for English Twitter users, negative emotion words were more common than positive ones in posts related to cyberbullying [39]. Nevertheless, another cyberbullying study that analyzed English Twitter posts collected in 2016 showed that the English users' attitude toward cyberbullying was largely neutral (43%, and "neutral" means not expressing any emotion), positive and negative attitudes toward cyberbullying were comparable (21%), and 16% had both positive and negative attitudes [32].…”
Section: Emotional Aspect Of Attitude Towards Cyberbullyingmentioning
confidence: 95%
See 2 more Smart Citations
“…The proportion of negative and positive emotions was 24.4% and 10.8%, respectively. Similarly, Tahamtan and Huang found that for English Twitter users, negative emotion words were more common than positive ones in posts related to cyberbullying [39]. Nevertheless, another cyberbullying study that analyzed English Twitter posts collected in 2016 showed that the English users' attitude toward cyberbullying was largely neutral (43%, and "neutral" means not expressing any emotion), positive and negative attitudes toward cyberbullying were comparable (21%), and 16% had both positive and negative attitudes [32].…”
Section: Emotional Aspect Of Attitude Towards Cyberbullyingmentioning
confidence: 95%
“…However, another study shows that Twitter users mainly have a negative attitude toward cyberbullying. Tahamtan and Huang used correlation network analysis and Bing's lexicon approach to explore topics and emotions in the discussion about cyberbullying, and found that people mentioned more negative words and discussed more cyberbullying prevention [39].…”
Section: Exploring Attitude With Natural Language Processing (Nlp) Te...mentioning
confidence: 99%
See 1 more Smart Citation
“…Informasi yang cukup memberikan bukti bahwa cyberbullying dapat muncul akibat dari latar belakang dan sudut pandang seseorang untuk berperilaku serta mengeksplorasi di sosial media (Rifauddin, 2016). Teks atau ucapan di media social berubah menjadi sesuatu yang menarik seseorang supaya mengejudge korban disosial media (Tahamtan & Huang, 2019).…”
Section: Pendahuluanunclassified
“…This approach is also reflected in the work done by [21] where the authors looked at tweets in Indonesia and discovered the terms and patterns used by bullies. [22] used text mining methods for English language and showed that "people", "kids", "students", "schools", and "stop" were most commonly used words -results that showed that many people were concerned with stopping the bullying behavior especially among the kids. [23] contended that adolescents tend to fall back on the trust between then and other individuals online and bullies tended to target the highly trusted relationship.…”
Section: Problem Descriptionmentioning
confidence: 99%